Sex and gender analysis in knowledge translation interventions: challenges and solutions - Amédé Gogovor; Tatyana Mollayeva; Nicole Etherington; Angela Colantonio; France Légaré; on behalf of the GIKT Group (BMC, 2020)
Abstract Sex and gender considerations are understood as essential components of knowledge translation in the design, implementation and reporting of interventions. Integrating sex and gender ensures more relevant evidence for translating into the real world. Canada offers specific funding opportunities for knowledge translation projects that integrate sex and gender. This Commentary reflects on the challenges and solutions for integrating sex and gender encountered in six funded knowledge translation projects. In 2018, six research teams funded by the Canadian Institutes of Health Research's Institute of Gender and Health met in Ottawa to discuss these challenges and solutions. Eighteen participants, including researchers, healthcare professionals, trainees and members of the Institute of Gender and Health, were divided into two groups. Two authors conducted qualitative coding and thematic analysis of the material discussed. Six themes emerged, namely Consensus building, Guidance, Design and outcomes effectiveness, Searches and recruitment, Data access and collection, and Intersection with other determinants of health. Solutions included educating stakeholders on the use of sex and gender concepts, triangulating perspectives of researchers and end-users, and participating in organisations and committees to influence policies and practices. Unresolved challenges included difficulty integrating sex and gender considerations with principles of patient-oriented research, a lack of validated measurement tools for gender, and a paucity of experts in intersectionality. We discuss our findings in the light of observations of similar initiatives elsewhere to inform the further progress of integrating sex and gender into the knowledge translation of health services research findings.